The Universality and Uniqueness of American, British, and Australian English Found in Youtube Platform - Desi Rahma Yuni Br.Sinulingga; Syahron Lubis (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2023)
The purpose of this research is to find the differences between the universality and uniqueness of American, British, and Australian English. The data for this research are videos found on the Youtube platform focused on American, British, and Australian English content. The method used in the analysis the data consisted of watching the videos carefully and observing them. It used the guidelines adaptation step designed by Alhamami (2013). The results of this research are: 1. the universality language found in American, British, and Australian English languages are in grammar, sound systems, suprasegmental sounds, and part of speech. 2. The uniqueness language found in American, British, and Australian English languages are in grammar focused on tenses, sound systems focussed on word stress, suprasegmental sounds focused on pronouncing words/dialects, and vocabulary differences.